“Efectos de fosfonato de calcio en el cultivo de lechuga (lactuca sativa L.) variedad de Lamas Waldeaman S strain-Provincia de Lamas” - Ore Aquino, Zoila Luz (2015)
This research work entitted "Effeets of eatcium _phosphonate GRO\MNG lETTUCE (Laciuca sativa) GRAND RAPIDS VARIETY WALDEMAN .. S STRAIN - Province LAMAS, "Aimed to detennine the best treatment effect of fOOar app!ication of calcium- phosphooate and pertonn economic analysis of the treatments under study, for which 4 treatments were evaluated: TO (no application)_, T1 (0-25 l ha-1af Catcium phosphanate), T2 (0.50 l.ha-1 of calcium phosphonate) and T3 {0.75 l.ha-1 of calcium phosphonate) T4 {1.0 l.ha-1 of calcium phosphonate}. The parameters evaluated were: diameter neck, floor length, number of leaves, plant weight, yield in t ha-1 production, economic analysis of all treatments studied. The mam condusfons were 1hat we obtafned m T3 (-0.75 kg_ ha-1 Ca phos_phooate} treatment obtained the highest average yield, plant weight and number of leaves per plant with 39,468-.8 kg ha-1, 157.9 g and 23.3 4eaves per ptant respectivefy staüsticaUy outperformmg the averages obtained by other treatments. The TO treatment obtained the lowest average yield., plant weight and .number af .leaves per p1ant with 27887.5 Kg,.ha-1, 11.6 g and 15.5 leaves per plant respectively. By the results of the evaluated variables where the maximum dose of phosphonate Ca (T 4) with 1.0 kg ha-1, did not exceed in average treatment with O. 75 kg ha-1 (T3), we can infer that the same or higher doses defined processes antagonism not keeping a good balance going to one of the nutrients has affected the absorption and utilization of other nutrients. The effect of the application of increasing doses of Ca phosphonate and agro-climatic conditions under which the research was conducted and the cultivation of the crQP otiettuee variety Grand Rapids Watdeman ·· s Strain, 1he T3 treatt11ent (0.75 kg. ha-1) obtained the highest value of B I C to 2.43 and net income per ha of S /. 18 589,41 soles, followed by T4 treatmem -(1-kg1&1), T2 (0.5-kg ha-1), T1 {0.25 kg ha-1) and TO (Control) those values of B I C 2,23; 2.1 O; 1,87; and 1,29 and net income of SI. 15 966~06; S/.14 296~29;. SI. 11 304,16 and S L 3 785,50 saJes respectiveJ.y.